Breath, eyes, memory - Danticat, Edwidge, 1969- (New York : Vintage Books, 1998)
Sophie Caco, a child who was born of rape, leaves Haiti at the age of twelve to join her mother in New York City, where they both battle with the results of sexual abuse.
"Originally published in hardcover by Soho Press, New York, 1994"--T.p. verso.
"Oprah's book club"--Cover.
Young Adult
Young Adult
750
Keywords: Haitian Americans -- New York (State) -- New York -- Fiction; Haitian Americans -- Travel -- Haiti -- Fiction; Women -- New York (State) -- New York -- Fiction; Mothers and daughters -- New York (State) -- New York -- Fiction; Haitian Americans -- Fiction; Women -- New York (N.Y.) -- Fiction; Mother-daughter relationship -- Fiction; Domestic fiction; Domestic fiction